1999
DOI: 10.1002/(sici)1097-0215(19991022)84:5<478::aid-ijc5>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of cd44 in metastatic prostate cancer

Abstract: Decreased expression of CD44 is an independent prognostic marker for surgically treated prostate cancer. To investigate immunohistochemically defined CD44 expression in primary and metastatic prostate cancer, 2 groups of patients undergoing radical prostatectomy for clinically localized prostate cancer were studied. (1) pN1 group: 23 patients, finally staged pN1, of whom the radical prostatectomy specimen and the lymph nodes were investigated to establish a correlation between CD44 expression in the concurrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 16 publications
(18 reference statements)
1
11
0
Order By: Relevance
“…Two other studies evaluated CD44. In 97 radical prostatectomy patients [29] with median followup of 84 months, utilizing PSA of >1.0 as failure, most (86%) patients were positive for CD44, so risk was determined by graded intensity of the staining. Decreased expression increased the risk of failure.…”
Section: Resultsmentioning
confidence: 99%
“…Two other studies evaluated CD44. In 97 radical prostatectomy patients [29] with median followup of 84 months, utilizing PSA of >1.0 as failure, most (86%) patients were positive for CD44, so risk was determined by graded intensity of the staining. Decreased expression increased the risk of failure.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of CD44 and its variants is associated with the progression of several cancers, although this remains controversial for CaP (De Marzo et al , 1998; Noordzij et al , 1999). One study reported a complete lack of membranous expression of all CD44 isoforms in 93–98% primary CaP tissues (Kallakury et al , 1996), whereas another reported moderate to high levels of CD44 expression in 60% of primary CaP, with ∼14% of metastases expressing low levels of CD44 (Nagabhusha et al , 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between CD44 expression and tumor grade is also uncertain -one study shows a strong correlation between Gleason grade of the tumor and loss of CD44 expression (De Marzo et al, 1998), whereas another reports no correlation (Paradis et al, 1998). Furthermore, although CD44 expression is reported to be reduced in metastases (Nagabhushan et al, 1996;De Marzo et al, 1998;Noordzij et al, 1999), the CD44 þ PCa cells are found to predominate in two visceral metastases (Liu et al, 1999). Similar to expression studies, the potential role of CD44 in PCa development and metastases is controversial -although some studies show a tumor-suppressive function of CD44 in overexpression experiments (Gao et al, 1997(Gao et al, , 1998, many other studies implicate CD44 in PCa cell proliferation, adhesion, migration, and invasion in vitro as well as in metastatic dissemination in vivo (Lokeshwar et al, 1995;Paradis et al, 1998;Liu et al, 1999;Draffin et al, 2004;Omara-Opyene et al, 2004).…”
Section: Introductionmentioning
confidence: 99%